Les groupes d’intérêt et la politique étrangère canadienne : le cas de l’Amérique centrale - Mace, Gordon; Roussel, Michel (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1990)
In the course of the 1980's studies on domestic sources of Canadian foreign policy have generated analytical propositions which, to this day, have not been submitted to empirical investigation. This paper presents the results of a case study on the domestic sources of Canadian foreign policy towards Central America for the period 1979-1987. The theoretical propositions underlying this study are taken from previous studies made by C. Pratt, J. Rochlin and S. Baranyi. By comparing the demands made by interest groups with the behavior, as observed, of the federal government, the authors show a relatively weak adequation between demands made by counter-consensus groups and governmental action towards Central America. The study also demonstrates a relatively minor interest on the part of the business groups in Canadian foreign policy towards Central America.